Die JV Stalin Works-kontroversie - Hendrich, Gustav (Faculty of the Humanities, University of the Free State, 2012)
During the apartheid era in South Africa many literary and creative book publications were declared undesirable and were banned by the organs of censorship. In the interests of state security communist publications were considered a threat in a state with a predominantly Christian-Calvinist religion and capitalist system. Publications by political figures such as Karl Marx, Vladimir Lenin and Joseph Stalin were banned in the early 1960s on account of their propagandist elements. In particular, strong objection was made against the writings of Stalin contained in his Works. Following the banning of Works this publication was out of bounds to the public for nearly two decades. As a result of internal changes in perception, as well as the management of publication control after 1977, the way was opened for the review of previously banned publications. Increasing pressure and pleas emanated from academic circles for freedom to consult historical sources for study and research purposes first hand. In 1982 there was an appeal case for lifting the ban on Works, which in fact throws light on the contentiousness around this work by Stalin. Since the ban on possession of this publication was lifted and it being fully unbanned in 1991, the successful appeal may be considered a victory for free expression and learning. It is the purpose of this article to describe and historically analyse the background of censorship under apartheid.
Keywords: Cencorship; Apartheid; South Africa; Publications control; Banning; Joseph Stalin; Communism; Freedom of opinion